From Problems to Progress: Improving Mathematics Learning Outcomes through Problem-Solving Instruction - Nguyễn, Minh Tuấn; Alorgbey, Bernard (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The aim of this research is to improve students' learning outcomes in Mathematics by using the Problem Solving method. Methodology: The research conducted used Classroom Action Research. Data were obtained from qualitative and quantitative data. Data collection techniques included observation, testing, documentation, and interviews. The data analysis method used both qualitative and quantitative data. Main Findings: Based on the results of data analysis, it is known that, after using the Problem Solving method, student learning outcomes have increased. This can be seen from the results of the pre-test and post-test given to students, which always increased in each cycle. The increase in student learning outcomes in cycle 1 was 71.88% and in cycle II 87.10%. There was an increase in the completeness of student learning outcomes by 5.31%. Novelty/Originality of this study: This study introduces a structured problem-solving instructional model implemented through classroom action research to regularly improve students' mathematics learning outcomes. Unlike previous studies, it integrates iterative reflection cycles with authentic classroom problems, providing practical evidence on how problem-solving instruction directly enhances students' engagement, conceptual understanding, and achievement.